Amicus curiae in enriching the consideration of judges when making decision on criminal case - Amanda Octavieni Bakhtiar; M. Raja Saputra. K; Dheny Wahyudhi (Green Governance: Exploring Politics, Social Justice, and the Environment, 2025)
Background: This study aims to determine and analyze how amicus curiae can enrich the consideration of judges' decisions to impose a criminal case decision and to determine and analyze the contribution of amicus curiae in criminal cases in Indonesian courts by Supreme Court Judges. Methods: The research method uses the Normative Juridical type, with in-depth analysis of several decisions, literature, journals, and doctrines. Findings: The results show that amicus curiae is not explained normatively in Indonesian legislation because it is a legal system adopted from the United States. Judges in handing down a decision can never be separated from the social desires demanded by reality, this makes judges have to carefully consider the decision of a case until an additional opinion from an amicus curiae is needed. It was found that amicus curiae as a "neutral" party was used by judges to be considered in handing down a case orally or in writing. Amicus curiae has participated in the development and decision of jurisprudence in the field of criminal law, where an amicus can state his statement both at the first, appellate and cassation court stages. Conclusion: The conclusion of this research shows that the contribution of amicus curiae can assist judges in carrying out their duties fairly and wisely. The existence of amicus curiae has been proven to be found in many criminal case decisions, both at the first instance, appeal and cassation stages. Although there are no basic rules governing its position in Indonesian legislation. Novelty/Originality of this article: This study provides a novel analysis of how amicus curiae, despite not being explicitly regulated in Indonesian legislation, has been utilized by Supreme Court judges in criminal case decisions.